Understanding the Influence of Geomagnetic Storms on Earth's Atmospheric Dynamics in April 2022 And 2023 - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2024)
Geomagnetic storms, which were brought on by solar activity in the ionosphere and thermosphere, influence the dynamics of Earth's atmosphere. This study aims to provide a comprehensive understanding of the effects of geomagnetic storms on many components of Earth's atmosphere. After summarizing the causes and characteristics of geomagnetic storms, such as solar flares and coronal mass ejections, the paper looks at how these events impact Earth's atmospheric dynamics. It focuses on the effects of geomagnetic storms on wind patterns, atmospheric temperature and density variations, thermospheric heating, and ionospheric disturbances. The study shows significant differences in the electric field strength over the first ninety-six days of April 2022 and 2023. Following this point, the electric field's behavior shows distinct tendencies, with notable differences between the two years. In April 2022, there was a slower fluctuation in the electric field strength following the initial rapid period. It reached its pinnacle around day 104, after which it started to deteriorate. In this pattern, a minimum was observed around day 106. A distinct pattern, however, is seen in April 2023, with a minimum electric field strength recorded at day 110 dipping below -2V/m and a sudden increase to a maximum of roughly 2V/m by day 113. The observed relative variations in mean electric field strength further explain the differences between April 2022 and April 2023. A relative change of -385.86 V/m highlights significant differences in electric field intensity between the two years and highlights the dynamic nature of atmospheric and ionospheric processes. The components of the magnetic field investigation, which revealed relative changes for mean Bx, By, and Bz of -267.01%, -9366.67%, and 57.14%, respectively, are consistent with these results. Together, these results demonstrate the intricate relationships between solar activity, geomagnetic disturbances, and atmospheric dynamics.